THE ROLE OF TRICHOMONAS TENAX IN PERIODONTAL DISEASE: A LITERATURE REVIEW - Nadia Nabiilah Rahmah Rayugi; Emma Rachmawati; Ina Hendiani (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: The oral cavity is a habitat for microorganisms such as bacteria, fungi, and protozoa. One of the most common protozoa found in the oral cavity is Trichomonas tenax. Imbalance between microorganisms and host in the oral cavity can cause periodontal disease. This study aims to determine the role T.tenax in periodontal disease. Review: This research is literature review by using the method rapid review of synthesizing and analyzing existing research. Article searches were conducted using the Pubmed, ScienceDirect, and EBSCOHost databases from November 2022 to February 2023. The research inclusion criteria were international journals from 2012 to 2022 which discussed the role of T.tenax with periodontal disease. Articles that met the inclusion criteria in this study were 5 articles. Articles proving that prevalence T.tenax higher in individuals with periodontal disease as many as 3 articles. 1 article proves that T.tenax have proteinases that play a role in the pathogenesis of periodontal disease. Articles which prove that the treatment of scaling and root planing can lower T.tenax there is 1 article. Conclusion: T.tenax found in individuals who have periodontal disease indicate that T.tenax role in the development of periodontal disease.